2015
DOI: 10.1167/iovs.14-15592
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Relative Amount of Hemoglobin in the Cup and Neuroretinal Rim Using Stereoscopic Color Fundus Images

Abstract: Visual field sensitivity was better correlated with Hb levels than with rim sector areas or the corresponding nerve fiber thickness. In many cases the remaining rim show low perfusion, especially in the superior and inferior sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 26 publications
2
50
0
1
Order By: Relevance
“…Several studies examined the agreement between subjective and objective VCDR assessment [5,[11][12][13][14][15] . In general, the value obtained from objective measurement is smaller than the clinically assessed VCDR, but some found the opposite to be true [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examined the agreement between subjective and objective VCDR assessment [5,[11][12][13][14][15] . In general, the value obtained from objective measurement is smaller than the clinically assessed VCDR, but some found the opposite to be true [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stereo photographs can be of help to assess disc morphology and stored for future reference [10] . These photos can be assessed by the clinician or analysed by specifically designed software [11] . The relationship and agreement between a clinical subjective (funduscopic) and technological objective assessment were investigated in multiple studies [5,[12][13][14][15][16] .…”
Section: Funduscopic Versus Hrt III Confocal Scannermentioning
confidence: 99%
“…No special importance was attached to equating the samples by age, since previous studies have shown no significant changes with age in the hemoglobin values of the ONH in normal subjects [11]. …”
Section: Methodsmentioning
confidence: 99%
“…New studies have allowed separating the rim from cup information, analyzing images obtained with a stereoscopic camera [11], and also associating two-dimensional photographic images with optical disk and cup delimitations provided by OCT [12]. Among the conclusions of these studies, two stand out: first, hemoglobin concentrations are better correlated with functional defects of glaucoma than the corresponding areas of the neuroretinal rim or RNFL thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of such a technique, 3D reconstruction of the Optic Nerve Head (ONH) in the retina can be mentioned. Figure 7 shows two examples of such an application by use of dense SIFT descriptors using the data provided as part of [65]. For each one of these examples, a pair of input images acquired from the left and right views of the ONH (first and second column) is captured, and the approximate depth information is retrieved (third column).…”
Section: Applications In Biomedical Image Processingmentioning
confidence: 99%